Improvement of response text writing skills through flow sentence techniques with image media in class IXA students at SMPN 3 Ngimbang - Hafidz Khoiri Budi Kuswoyo (Journal of diversity in learning (JDIL), 2021)
The purpose of this study is to describe the learning process of writing descriptive response text, describe changes in spiritual attitudes, describe changes in social attitudes, describe the increase in knowledge of learners, and describe the improvement of learning skills to write descriptive response text through flowing sentence techniques with image media in students of grade IX. The learning process is carried out through two cycles, namely cycle I and cycle II. The results showed that the average grade score in the precyclical knowledge test was 62.97. In cycle I it increased by 66.81 or in a fairly good category and in cycle II increased again by 82.81 or in either category. The results of the pre-cycle skills test were 66.5 or in a fairly good category. In cycle I it increased by 77.2 and in cycle II increased again by 84.3. Improved writing of descriptive response text was also followed by a change in learners' learning attitudes in a better direction during the learning process of writing descriptive response text through flowing sentence techniques with image media.